Emerging risk factors for cardiovascular diseases: Indian context - Gupta, Sushil (Medknow Publications & Media Pvt Ltd, 2013)
Cardiovascular disease (CVD) is globally considered as the leading cause of death with 80% of CVD related deaths being reported from low and middle income countries like India. The relatively early onset age of CVD in India in comparison to Western countries also implies that most productive ages of the patient's life are lost fighting the disease. Conventional cardiovascular risk is attributed to lifestyle changes and altered metabolic activity. This forms the basis of a 10-year risk prediction score inspired by the Framingham study. Since South Asians display considerable heterogeneity in risk factors as compared to developed countries, there is a need to identify risk factors which would not only help in primary prevention but also prevent their recurrence. We reviewed published data on novel risk factors and their potential to identify cardiovascular risk at an early stage, with special emphasis on the Indian population. Emerging risk factors were reviewed to identify their potential to prevent CVD progression independently as well as in association with other cardiovascular risk factors. The most commonly studied emerging cardiovascular risk factors included coronary artery calcium score, lipoprotein (a), apolipoproteins, homocysteine, thrombosis markers like fibrinogen, and plasminogen activator inhibitor 1, carotid intima-media thickness, genotypic variations, non-alcoholic fatty liver disease, C-reactive protein, platelets, and birth weight levels. Nonetheless, more studies on large sample size can ascertain the utility of these risk factors in estimation and analysis of cardiovascular risk especially in the Indian context.